Angiotensin II, Cell Proliferation and Angiogenesis Regulator: Biologic and Therapeutic Implications in Cancer - Escobar, Elizabeth; Rodriguez-Reyna, Tatiana S.; Arrieta, Oscar; Sotelo, Julio (Current Vascular Pharmacology, 2004)
Angiotensin II (ANG II) is the main effector peptide in the renin-angiotensin system. It is generated by the activation of Angiotensin I through the Angiotensin II Converter Enzyme (ACE II). ANG II has multiple physiologic effects that regulate vascular tone, hormone secretion, tissue growth and neural activity. It has systemic (endocrine) and local (paracrine and autocrine) effects, favoring cell growth and differentiation through four types of receptors from which types 1 and 2 (AT1 and AT2) are the most important. Stimulation of AT1 leads to the activation of intracellular pathways that finally lead to vasoconstriction, inflammation and proliferation. The AT2 receptor is mainly expressed in fetal tissue and scantly in the cardiovascular system under different circumstances. Its effects are opposite to those of the AT1. The stimulation of AT1 activates second messengers that lead to a rapid production of diacylglycerol and 1-4-5-inositol triphosphate, as well as to the activation of C protein. Several reports indicate that ANG II can induce neovascularization in experimental systems due to the expression of different growth factors such as angiopoietin 2, vascular endothelial factor, and its receptor, fibroblast growth factor, platelet derived growth factor, transforming growth factor β and epidermal growth factor. Other mechanisms associated with ANG II induced angiogenesis are nitric oxide synthase and metalloproteinase expression, as well as inflammation induction. Angiogenesis is a fundamental process to tissue repair and development, and it participates in several pathologic processes. In addition, the AT1 receptor is expressed in many malignant neoplasms and its blockade through ECA II inhibitors and ANG II antagonists has shown antineoplastic activity as well as angiogenesis inhibition in tumoral experimental models. This review discusses the mechanisms by which ANG II participates in neoplastic and non-neoplastic tissue angiogenesis and its possible therapeutic implications.
Keywords: angiogenesis